In India and East Africa = E-Indiya nase East Africa : A travelogue in isiXhosa and English - Jabavu, Davidson D. T. (Davidson Don Tengo), 1885-1959 (Wits University Press, 2020)
This volume includes D.D.T. Jabavu's account of his journey to India in 1949, in the original isiXhosa and with an English translation by Cecil Wele Manona. Chapters by the volume editors provide biographical context for the travelogue, and commentary on its contribution to the archive of African-language literature and thought.